The Role of Fintech in Financial Inclusion (Case Study of MSME Entrepreneurs in Surabaya) - Nursansiwi, Dwi Arini; Armiani, Armiani (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate the influence of certain factors on financial inclusion in Micro, Small and Medium Enterprises (MSMEs) in the City of Surabaya. The quantitative analysis method was used by collecting data through questionnaires from 100 respondents who were MSME owners. The research results show that financial risk factors have a positive and significant influence on financial inclusion, while the perceived usefulness and trust factors do not have a significant influence. These findings provide important insights for stakeholders in designing policies that support MSME financial inclusion in the city of Surabaya.